Strategies for Increasing the Competitiveness of MSMEs in the Digital Economy Era: A Study of Spicy Soy Sauce Chicken MSMEs - Siti Nur Aini; Wahyu Alya Larasati; Arti Widyaningsih (Escalate : Economics and Business Journal, 2026)
MSMEs play an important role in Indonesia's economy but face significant challenges in adapting to digital transformation. This study aims to analyze opportunities and formulate strategies to enhance the competitiveness of MSMEs in the digital economy era, using a case study of the “Ayam Kecap Pedas” (AKP) MSME in Magelang. The research employs a descriptive qualitative approach with a case study strategy. Data collection techniques include observation, document analysis, and interviews. The results identify several key opportunities, such as broader market access through e-commerce, operational efficiency through digitalization, and government support programs. Based on these findings, strategies for enhancing competitiveness are formulated in four main aspects: (1) operational system digitalization through the implementation of POS systems and digital literacy training; (2) marketing digitalization through social media optimization, digital promotions, and expanding e-commerce partnerships; (3) improvement of internal management; and (4) service innovation. The implementation of these strategies is expected to strengthen the competitiveness of AKP MSME and serve as a reference model for similar culinary MSMEs in adapting to the digital era.